Modification of the structural and functional properties of wheat gluten protein using a planetary ball mill. (30th November 2021) - Liu, Ziqiao; Zheng, Zhi; Zhu, Guobin; Luo, Shuizhong; Zhang, Danfeng; Liu, Fengru; Shen, Yizhong
Highlights: Planetary grinding changed the conformation structure of wheat gluten protein. The number of free sulfhydryl group and protein surface hydrophobicity index increased. Emulsifying and foaming properties of wheat gluten were improved ( p < 0.05). Mechanical force of mill reduced particle size and increased whiteness ( p < 0.05). Planetary ball milling technology has great potential for protein modification. Abstract: The modification of the structure and function of wheat gluten because of planetary ball milling was investigated. Reduced SDS-PAGE revealed that the subunit compositions and bands of gluten did not change with an increase in grinding time. FTIR analysis showed that α-helices and β-sheets decreased, whereas β-turns increased, indicating that the secondary structure of gluten became looser and more disorderly. Owing to the mechanical force of planetary ball milling constantly breaking the disulfide bonds in gluten, the number of free sulfhydryl groups increased, and surface hydrophobicity increased from 940.97 to 1197.50 after 20 min ball-milling treatments, whereas the foaming capacity was improved from 8.7 to 31 cm 3 . After 40 min, mastersizer analysis showed that particle size decreased from 85.9 to 32.3 μm, and the whiteness increased from 49.51 to 65.59. These results indicate that planetary grinding technology improves the functional properties of wheat gluten and expands its application potential.